Investigation of the differential susceptibility of extraocular muscles in patients diagnosed with ocular myasthenia gravis based on the computerized diplopia test and the Ocular Motor Nerve Palsy Scale - Fan, Yi-fei; Tu, Sai-jun; Liu, Yani; Li, Xue-mei; Liu, Tie-juan; Zhou, Ling-yun (Frontiers in Neurology, 2024)
Introduction The pattern of extraocular muscle involvement in ocular myasthenia gravis varies across different reports, diverging from our own observations. Thus, we employed two novel tools to discern this pattern. Methods A retrospective analysis was conducted to collect and organize clinical data from 43 patients diagnosed with ocular myasthenia gravis. Each patient underwent both the computerized diplopia test and the Ocular Motor Nerve Palsy Scale assessment to evaluate the involvement of extraocular muscles. Results Among the patients, there were 30 male and 13 female individuals, with a total of 113 affected extraocular muscles identified. Among all the affected extraocular muscles, the involvement of the levator palpebrae superioris muscle accounted for 35.40%, medial rectus muscle 7.7%, lateral rectus muscle 16.81%, superior rectus muscle 13.27%, inferior rectus muscle 12.39%, superior oblique muscle 1.77%, and inferior oblique muscle 2.65% of the total affected extraocular muscles. The positivity rates of the Neostigmine test were 89.19%, AChR antibody detection was 59.38%, and repetitive nerve stimulation was 34.38%. The AChR antibody positive rate among patients with only diplopia was 100%; among those with only ptosis, it was 80%; and among those with both diplopia and ptosis, it was 86.67%. Conclusion The involvement of the extraocular muscles is not uniform. The levator palpebrae superioris exhibits the highest incidence rate, followed by the four rectus muscles and two oblique muscles. The inferior oblique involvement typically occurs when four or more EOMs are affected. Moreover, the levator palpebrae superioris and medial rectus show a higher tendency for bilateral involvement compared with other extraocular muscles.